Pemanfaatan Bubuk Kulit Sukun (Artocarpus altilis) Sebagai Adsorben Pemurnian Minyak Jelantah - Rusna, Rusna; Sami, Muhammad; Rihayat, Teuku (Politeknik Negeri Lhokseumawe, 2024)
Cooking oil is used by the general public to produce waste known as used cooking oil, both in households and small or large industries. The procedure most often used to manage used cooking oil waste is purification. Adsorption with adsorbents is an effective and efficient used cooking oil purification process. Adsorption with breadfruit peel powder is one method for removing used cooking oil. The aim of this research is to determine the absorption capacity of breadfruit peel adsorbent (Artocarpus altilis) on used cooking oil originating from fast food restaurants by using a heating process as well as the mass and temperature of the best breadfruit peel (Artocarpus altilis) adsorbent that can purify used cooking oil. The results of this research were the use of breadfruit (Artocarpus altilis) peel powder adsorbent with a mass of 8; 9; 10; 11 and 12 grams by varying the temperature 80; 85; 90; 95; 100oC and heating time 45 minutes. Adsorption products were analyzed for water content, peroxide value and free fatty acids. The best water content is at a temperature of 100oC, namely 0.07%; 0.06%; 0.07%; 0.05% and 0.03% with an initial water content of 2.46%, the best peroxide value is at a temperature of 100 oC with a mass of 11 grams, namely 8 mek/g with an initial peroxide value of 30 mek/g and the best free fatty acids at a temperature of 100 oC with an adsorbent mass of 12 grams of 0.20% with an initial free fatty acid of 1,33% .